Buffering new risks? Environmental, social and economic changes in the Turkana Basin during and after the African Humid Period. (December 2022) - Hildebrand, Elisabeth; Grillo, Katherine M; Chritz, Kendra L; Fischer, Markus L; Goldstein, Steven T; Janzen, Anneke; Junginger, Annett; Kinyanjui, Rahab N; Ndiema, Emmanuel; Sawchuk, Elizabeth; Beyin, Amanuel; Pfeiffer, Susan K
This paper evaluates risk-oriented frameworks for explaining environmental, social, and economic changes faced by fishing and herding communities in the Turkana Basin during and after the African Humid Period (AHP, 15–5 ka). The orbitally-forced AHP created moist conditions, high lake levels, and unusual hydrological connections across much of northern and eastern Africa. As arid conditions set in and rainfall decreased between 5.3 and 3.9 ka in eastern Africa, Lake Turkana (NW Kenya) shrank dramatically. Shoreline retreat coincided with an expansion of open plains, creating new ecological conditions and potential opportunities for early herders in the basin. In this changing landscape, economies shifted from food procurement (fishing/hunting aquatic resources) to food production (herding), likely through both in-migration by pastoralists and adoption of herding by local fishers. Early pastoralists also built at least seven megalithic pillar sites that served as communal cemeteries during this time. Recent research has shown that local environmental dynamics – both during and after the AHP – were complex, demanding a more careful interrogation of the notion that post-AHP life entailed new and/or heightened risks. Risk-buffering strategies might include mobility, diversification, physical storage, and exchange. Archaeologists working around Lake Turkana have proposed that economic shifts from fishing to pastoralism entailed increased mobility as a risk-buffering strategy to deal with aridity and resource unpredictability, and that pillar sites – as fixed landmarks in an unstable landscape – provided settings for congregation and exchange amongst increasingly mobile herding communities. However, recent research has shown that local environmental dynamics in the Lake Turkana basin – both during and after the AHP – were more complex than previously thought, necessitating re-evaluation of the notion that post-AHP life entailed new and/or heightened risks. Here, we explore risk buffering strategies (e.g. mobility, diversification, physical storage and/or exchange) as only one category of potential explanation for the new social practices observed in the region at this time. Gauging their applicability requires us to (a) assess the spatial mobility of communities and individuals interred at pillar sites; (b) evaluate whether and how mobility strategies may have changed as pastoralism supplanted fishing; and (c) examine alternative explanations for social and economic changes.